Longitudinal Change in Myocardial Function and Clinical Parameters in Middle-Aged Subjects: A 3-Year Follow-up Study - Cho, Dong-Hyuk; Joo, Hyung Joon; Kim, Mi-Na; Kim, Hee-Dong; Lim, Do-Sun; Park, Seong-Mi (Diabetes & metabolism journal, 2021)
Background: Metabolic syndrome (MetS) is closely associated with the aging process. However, changes in metabolic conditions and cardiac function that occur in middle aged population remain unclear. We evaluated longitudinal changes in metabolic parameters and cardiac function during a 3-year period in subjects with suspected MetS.Methods: We studied 191 participants with suspected MetS at baseline and after 3 years. Anthropometric parameters, including waist circumference (WC), and metabolic parameters, including fasting blood glucose and lipid profile were measured. Conventional echocardiography with two-dimensional speckle tracking was performed.Results: Mean age was 56.2±4.4 years, and there were 97 women (50.8%). Men had increased WC and triglycerides (TG) (WC 91.2±6.8 cm vs. 84.0±8.0 cm, P<0.001; TG 184.4±116.3 mg/dL vs. 128.2±53.6 mg/dL, P<0.001), and reduced global longitudinal strain (GLS) (–15.4%±2.1% vs. –17.1%±2.0%, P<0.001) compared to women. After 3.4 years, values of WC and TG did not change in men but increased in women (all P<0.05). The absolute value of left ventricular (LV) GLS did not change in men but was reduced in women (P=0.011). Change in TG was independently associated with worsening of LV GLS only in women (standardized β, –0.309; 95% confidence interval, –0.130 to –0.009; P=0.025).Conclusion: In middle aged population, a vulnerable period for metabolic disturbance, cardiac remodeling tended to progress, which was prominent in women. Progression of adiposity and dyslipidemia after menopause may accelerate subclinical cardiac remodeling in middle-aged women. Lifestyle modification and medical interventions may help prevent further cardiac dysfunction in these subjects.